Patterns of caesarean-section delivery in Addis Ababa, Ethiopia - Yibeltal T. Bayou; Yohana J.S. Mashalla; Gloria Thupayagale-Tshweneagae (AOSIS, 2016)
Setting: The study was conducted in Addis Ababa, the capital city of Ethiopia. Specifically, it was conducted in all healthcare facilities offering maternity and obstetric services. Objective: The objective of the study was to explore the patterns of caesarean-section (CS) delivery in Addis Ababa. Methods: A cross-sectional survey was carried out between December 2013 and January 2014. The population for the study were women aged between 15 and 19 years of age who had given birth in the last 1-3 years before the date of data collection. The Census and Survey Processing System software was used for data capturing and analysing both descriptive and inferential statistics using Statistical Package for Social Sciences version 20.0. Results: Amongst the 835 women who delivered at health facilities, 19.2% had given birth by CS. The prevalence of CS based on medical indication was 91.3%. However, 6.9% of CS performed had no medical indication. Private health facilities performed more CSs than public health facilities, 41.1% and 11.7% respectfully. CS was high amongst women of higher socioeconomic standing. Conclusion: Overall, CS deliveries rate in Ethiopia is above the rate recommended by the World Health Organisation. Because socio-economic factors influence CS delivery, governments should play a key role in regulating performance of CSs in private institutions.